PROFESSOR E. WASKOWSKI: THE OBJECTIVES AND PRINCIPLES OF CIVIL PROCEDURE - Nekrošius, Vytautas (Teisė, 2017)
The article analyses the doctrine of the objectives and main principles of civil procedure established by prof. E. Waskowski. It is proved that professor was one of the first European scientists, who recognised the social function of civil procedure and an assertion that one of the objectives of civil procedure is based on public interests. Prof. E. Waskowski was one of the most famous scientists in legal community in the turn of 19th century. He worked in Vilnius University (known as University of Steponas Batoras at that time) for a great part of his life, concentrating his scientific career on Civil Procedure law.